Transcriptome Analysis of Aedes albopictus (Diptera: Culicidae) Larvae Exposed With a Sublethal Dose of Haedoxan A. Issue 6 (17th May 2021) - Hao, Huanhuan; Zuo, Yayun; Fang, Jiameng; Sun, Anqi; Aioub, Ahmed A A; Hu, Zhaonong
Abstract: Aedes albopictus is the vector of arbovirus diseases including yellow fever, dengue, Zika virus, and chikungunya fever, and it poses an enormous threat to human health worldwide. Previous studies have revealed that haedoxan A (HA), which is an insecticidal sesquilignan from Phryma leptostachya L., is a highly effective natural insecticide for managing mosquitoes and houseflies; however, the mechanisms underlying the response of Ae. albopictus after treatment with sublethal concentrations of HA is not clear. Here, high-throughput sequencing was used to analyze the gene expression changes in Ae. albopictus larvae after treatment with the LC30 of HA. In total, 416 differentially expressed genes (DEGs) were identified, including 328 upregulated genes and 88 downregulated genes. Identification and verification of related DEGs were performed by RT-qPCR. The results showed that two P450 unigenes ( CYP4C21 and CYP304A1 ), one carboxylesterase, and one ABC transporter ( ABCG1 ) were induced by HA, which indicated that these detoxifying enzyme genes might play a major role in the metabolic and detoxification processes of HA. Additionally, acetylcholine receptor subunit ɑ2 ( AChR α 2 ), AChR α 5, AChR α 9, and the glutamate receptor ionotropic kainate 2 ( GRIK2 ) were found to be upregulated in HA-treated larvae, suggesting that HA affected the conduction of action potentials and synaptic transmission by disrupting the function of neural receptors. These results provide a foundation for further elucidating the target of HA and the mechanism of detoxification metabolism in Ae. albopictus.